Bark stripping caused by the introduced squirrel Callosciurus erythraeus (Sciuridae) in Argentina - Pedreira, Paula A; Penon, Eduardo; Borgnia, Mariela (BOSQUE, 2017)
An assessment of bark stripping damage caused by the introduced red-bellied squirrel (Callosciurus erythraeus) was carried out in the area where this rodent is currently established in Argentina. The study was carried out in four forested areas, on 38 plots of 150 and 250 m2, where damaged species, type and intensity of the damage were recorded. Squirrel severely debarked 12 forest species and 57 % of sampled trees showed wounds below 5 m. Results showed that the red-bellied squirrel can be considered a harmful species for forests in the study area and could be a potential problem to other regions of Argentina if it continues its invading dispersal. The implications to forest production were discussed.